Monitoring of Zinc level in Milk of Breastfeeding Mothers at First Month of Delivery - Mohammad Hossien Salmani Nodoushan; Zinab Rezai; valiallah Nassiri; Farokhlegha Servat; Mahdieh Delikhoon (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: Zinc plays a vital role in various biological functions and physical growth. More than 300 enzymes in body need zinc for proper function. In this study, the concentration of the zinc micronutrient in breast milk was evaluated and analyzed at the first month of breastfeeding. Materials and Methods: This was a descriptive study of 150 breastfeeding mothers in the 2014 who had given birth in Yazd and were sampled in a simple way. Sampling was done exclusively in the health and treatment centers in the city, in the spring of 2014. 10- 20 ml samples of breast milk were taken manually in the morning and before infants' feeding, in 3 times of 5, 15 and 30 days after delivery, to measure the micronutrient of zinc. The concentration of zinc was measured by atomic absorption spectroscopy.Data obtained by questionnaires and atomic absorption was analyzed by ANOVA test. Results: The average age of mothers was 27.40 ± 4.67 years. The average level of zinc in breast milk was 2.60 ± 0.35 mg/l. The zinc concentration of breast milk was at the bottom of the standard range of zinc in breast milk.There was no significant relationship between zinc averages in milk with education, age, BMI and mothers' job. But, there was a direct relationship between zinc levels of breast milk with mothers' BMI. Conclusion: According to the results of this study, it seems that addition of zinc to the diet of breastfeeding mothers helps to prevent zinc deficiency in mothers' blood serum as well as children's nutrition.